Outcome of Acetaminophen‐Induced Acute Liver Failure Managed Without Intracranial Pressure Monitoring or Transplantation. Issue 1 (4th January 2019) - Porteous, Jennifer; Cioccari, Luca; Ancona, Paolo; Osawa, Eduardo; Jones, Kelly; Gow, Paul; Angus, Peter; Warrillow, Stephen; Bellomo, Rinaldo
Abstract : Acetaminophen‐induced acute liver failure (ALF) may require emergency liver transplantation (LT) in the presence of specific criteria, and its management may also include intracranial pressure (ICP) monitoring in selected patients at high risk of cerebral edema. We aimed to test the hypothesis that management of such patients without ICP monitoring or LT would yield outcomes similar to those reported with conventional management. We interrogated a database of all patients treated in an intensive care unit for acetaminophen‐induced ALF between November 2010 and October 2016 and obtained relevant information from electronic medical records. We studied 64 patients (58 females) with a median age of 38 years. Such patients had a high prevalence of depression, substance abuse, or other psychiatric disorders and had ingested a median acetaminophen dose of 25 g. No patient received ICP monitoring or LT. Overall, 51 (79.7%) patients survived. Of the 42 patients who met King's College Hospital (KCH) criteria, 29 (69.0%) survived without transplantation. There were 45 patients who developed severe hepatic encephalopathy, and 32 (71.1%) of these survived. Finally, compared with the KCH criteria, the current UK Registration Criteria for Super‐Urgent Liver Transplantation (UKRC) for super‐urgent LT had better sensitivity (92.3%) and specificity (80.4%) for hospital mortality. In conclusion, in a center applying a no ICP monitoring and no LT approach to the management of acetaminophen‐induced ALF, during a 6‐year period, overall survival was 79.7%, and for patients fulfilling KCH criteria, it was 69.0%, which were both higher than for equivalent patients treated with conventional management as reported in the literature. Finally, the current UKRC may be a better predictor of hospital mortality in this patient population.